AES (Advanced Encryption Standard) and RSA (Rivest Shamir Adleman) Encryption on Digital Signature Document : A Literature Review: Watermarking, Digital Signature, AES, RSA, Literature Review - Riko Yudistira (Universitas Kristen Satya Wacana, 2024)
Distributed digital documents, it can utilize cryptographic methods to provide confidentiality, data integrity, authentication and non repudiation services. Watermark in this case serves as authentic proof of ownership of the data or document, and its existence should not damage or change the contents or counter of digital data or digital documents. The RSA and AES encryption methods in digital signatures are appropriate to be taken as a reliable method. But a unique biometric key idea emerged, one of which was used to authenticate users.